Trustless education? A blockchain system for university grades. - ROOKSBY, JOHN; DIMITROV, KRISTIYAN (Ubiquity (2045-6271), 2019)
We have implemented a blockchain system based on Ethereum for use by a university to store student grades and to provide a cryptocurrency. Based upon an exploratory, qualitative evaluation we have found several tensions between the concept of a university as an organization and the concept of distributed autonomous organizations (DAOs) in Ethereum. These include tensions in (i) mechanisms of trust, (ii) boundaries of openness and (iii) values in procedures. In this article we outline our implementation and the evaluation process.